Farmers hesitant to use tea plucking machines - Wainaina Ndung'u (Nairobi The Standard Group Ltd, 2012)
Farmers say that adoption of tea plucking machines has been associated with low quality production in tea sector.
Keywords: Farm automation -- tea plucking machines; Tea industry -- Kenya